Islamic Education Curriculum That is Relevant to the Challenges of the Times - Baharuddin, Baharuddin; Isnaini, Ellychia; Lusiana, Lusiana (East Asian Journal of Multidisciplinary Research, 2024)
Presently, Islamic education is confronted with intricate challenges that stem from internal and external sources. The objective of this article is to furnish insights into the current challenges and demands encountered by Islamic education, along with curriculum development strategies that can effectively address these issues. Utilised is qualitative descriptive analysis as the methodology. Information was acquired via a comprehensive review of the literature, encompassing authoritative papers, scientific journals, pertinent to the topic under investigation. The findings of this study indicate that Islamic education is presently confronted with obstacles emanating from both internal and external domains. An Islamic schooling. Islamic education faces the following internal obstacles: the fulfilment of the eight national education standards; the demographic dividend, which is increased by Indonesia's population growth; and character issues. The external obstacles that Islamic education must contend with are more prospective in nature. Islamic education is necessary in order to address contemporary societal issues, foster the development of the creative and cultural sectors, prepare for future demands, and facilitate the internationalisation of education.